How does Central Environmental Protection Inspection drive the green transformation of China’s heavy-polluting enterprises from an ESG perspective? - Wang, Wanting; Mao, Chong; Liu, Shenya (Frontiers in Environmental Science, 2024)
The green transformation of heavy polluting enterprises under the Carbon Peaking and Carbon Neutrality Goals needs the escort of command environmental regulation. This paper takes the first round of central environmental supervision as a natural experiment, reflecting the degree of green transformation through the ESG (environmental, social, and governance) level of enterprises. Taking Chinese A-share listed companies in Shanghai and Shenzhen from 2010 to 2022 as the research object, a dual machine learning model is used to find that this system can improve the ESG level of enterprises and promote their green transformation. Using a dual machine learning model, it is found that the system can enhance the ESG level of enterprises and promote their green transformation. Mechanism analyses show that the system promotes green transformation by enhancing green innovation capability, safeguarding the rights and interests of upstream and downstream supply chain actors, and enhancing governance diligence, thus encouraging enterprises to assume environmental, social and governance responsibilities. It is also found that at the macro-policy level, with the migration of the inspection area to the west and the strengthening of local environmental governance, and at the micro-firm level, the higher the degree of digitisation and the larger the size of assets, the system's effect on the green transformation of heavy polluting enterprises deepens. It is further found that the spillover effect of green transformation within industries strengthens the positive effect of the Central Environmental Protection Inspections on enterprises' green transformation compared to inter-industry.